Rum Punch and Revolution: Taverngoing and Public Life in Eighteenth-Century Philadelphia - Campbell, Robert A. (Labour / Le Travail, 2001)
The article reviews the book, "Rum Punch and Revolution: Taverngoing and Public Life in Eighteenth-Century Philadelphia," by Peter Thompson.